Thomas More through temporary museum exhibitions - Burgos Ávila, Isabel (Moreana, 2024)
The pedestal of the statue of Thomas More by Leslie Cubitt Bevis, unveiled in 1969 in Chelsea, includes three inscriptions: statesman, humanist, saint. The person of More and his particularly renowned qualities have been celebrated by at least 20 temporary exhibitions, held in eight different countries, between 1896 and 2024. The standard of these exhibitions reflects the intellectual pre-eminence of the personalities involved in them, as well as the prestige of the institutions in which they have been held. The enduring significance of More is indicated by the high number of visitors to these exhibitions, as well as the attendance of authorities such as Queen Elizabeth II of the United Kingdom, Queen Mathilde of the Belgians, the president of the Council of Ministers of the Italian Republic, Mario Monti, and the president of the Pontifical Council for Promoting the New Evangelization, Monsignore Rino Fisichell.